PROTECTION OF SUPPLIERS OF AGRICULTURAL AND FOOD PRODUCTS FROM UNFAIR TRADING PRACTICE - Micovic, Andrej (Economics of Agriculture, 2021)
The paper analyses unfair trading practices that arise as a result of imbalance in bargaining power between suppliers and buyers of agricultural and food products. Considering that unfair practices also exist in the relations established between consumers and traders, that special rules have been adopted in this regard, the peculiarities and differences that exist between these rules were first pointed out, i.e., in terms of the approach to regulating these practices. Furthermore, the classification of unfair trade practices as absolutely and relatively prohibited was performed, and, finally, the rules on the way in which suppliers are protected from unfair practices were set out. Basically, the method of protection (administrative protection, at the initiative of the competent authorities or at the request of relevant organizations and associations) justifies the adoption of special rules that establish an effective system of protection of suppliers from unfair trading practices.